CATAGENESIS OF RIPHEAN AND VENDIAN DEPOSITS IN WESTERN BASHKORTOSTAN AND REALIZATION OF THE HYDROCARBON POTENTIAL OF THEIR ORGANIC MATTER: NUMERICAL ESTIMATES - Galushkin Yu.I.; Yakovlev G.E.; Kuprin V.F. (My University, 2004)
Thermal maturation of organic mater in the Precambrian sedimentary rocks of western Bashkortostan and realization of their oil-gas generation potential were numerically estimated using a chemical kinetic model for the maturation of nonmarine type II kerogen considering first- and second-order reactions for an initial hydrocarbon generation potential of 377 mg/g Corg. The calculations were carried out for sedimentary sequences penetrated by drill holes along two latitudinal and one longitudinal profile. The calculations indicate that catagenesis temperature and organic matter maturation increase in the sequences along with basement deepening toward the Ural Fold Belt. For example, in the western part of the region (Morozovskaya area), the basement occurs at a depth of 2.5 km, where the catagenesis temperature is not higher than 70°C and the hydrocarbon generation potential of the Riphean rocks was realized by less than 0.5%. In contrast, in its eastern part (Yuzhno-Taftinskaya and Leuzskaya areas), the basement occurs at depths of greater than 14 km, where catagenesis temperature probably exceeded 150-180°C. As a result, the hydrocarbon generation potential of the Lower Riphean rocks was completely realized, and liquid hydrocarbons were partly decomposed to form gas and coke owing to secondary cracking. With respect to OM maturation conditions, the Middle-Late Riphean and Late Vendian rocks of the eastern part of the region can be regarded as oil-generating. Unlike the models based on the temperature-time index or kinetic spectra of type III kerogen, the vitrinite reflectance and kinetic spectra of vitrinite maturation yield reasonable estimates for the degree of catagenesis of Riphean and younger rocks.
Keywords: Riphean; Vendian; Precambrian::Proterozoic::Riphean; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский; Докембрий::Протерозой::Рифей